Darboux Transformations and Soliton-Like Solutions of a New System Associated with the Negative AKNS System - Shilong Huang; Hongmin Li (Advances in Mathematical Physics)
In this letter, we consider a new two-component system. By its reciprocal relation with the first negative flow in the AKNS hierarchy, we construct three Darboux-Bäcklund transformations for the new system and obtain some soliton-like solutions.